2001
DOI: 10.1095/biolreprod64.2.647
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediamine-N,N,N′,N′-Tetraacetic Acid Induces Parthenogenetic Activation of Porcine Oocytes at the Germinal Vesicle Stage, Leading to Formation of Blastocysts1

Abstract: The present study showed that treatment with a cell membrane-impermeable metal ion chelator, EDTA, of porcine oocytes at the germinal vesicle (GV) stage collected from follicles 2-6 mm in diameter induced artificial activation followed by formation of a pronucleus (PN). When the oocytes were cultured for 48 h in medium containing 0.1 to 2 mM EDTA disodium salt (Na-EDTA), they were activated to form PN, and the maximum PN formation rate (63%, n = 68) was achieved in oocytes cultured with 1 mM Na-EDTA. More than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Historically, Azuma et al . [ 3 ] were the first to report that porcine GV-stage oocytes can be parthenogenetically activated by treatment with Na-EDTA during maturation culture, inducing PN formation, followed by blastocyst formation. Moreover, they demonstrated that Ca-EDTA treatment could also activate porcine oocytes and induce precocious PN formation during oocyte meiosis [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, Azuma et al . [ 3 ] were the first to report that porcine GV-stage oocytes can be parthenogenetically activated by treatment with Na-EDTA during maturation culture, inducing PN formation, followed by blastocyst formation. Moreover, they demonstrated that Ca-EDTA treatment could also activate porcine oocytes and induce precocious PN formation during oocyte meiosis [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] were the first to report that porcine GV-stage oocytes can be parthenogenetically activated by treatment with Na-EDTA during maturation culture, inducing PN formation, followed by blastocyst formation. Moreover, they demonstrated that Ca-EDTA treatment could also activate porcine oocytes and induce precocious PN formation during oocyte meiosis [ 3 , 4 ]. They suggested that the treatment of porcine oocytes with Ca-EDTA leads to a deficiency of extracellular Zn 2+ , alters the composition of the membrane and modifies intracellular conditions, eventually resulting in the promotion of parthenogenetic development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial stimuli that elevate the cytoplasmic levels of calcium ions can induce activation of oocytes even without penetration by sperm (For review see KAUFMAN, 1983). A wide spectrum of activating stimuli, e.g.including ionophore, ethanol, electrical pulses, and other chemicals, is used to induce artificial activation of mammalian eggs (PRATHER et al, 1997;GRUPEN et al, 1999;AZUMA et al, 2001;JILEK et al, 2001;). However, the search for other suitable methods continues The present study was designed 1) to determine the effectiveness of two oocyte maturation media, 2) to compare the effect of two fertilization media on the developmental competence of pig oocytes, and 3) to test the activation ability of pig oocytes matured in the two maturation media, electroactivated, and cultured in mSOFaa.…”
Section: Introductionmentioning
confidence: 99%